In the shadows: nasopharyngeal tuberculosis as adenoid hypertrophy in adult - Bajwa, Dilpreet; Tatavarthy, Shashidhar; Chandra, Indresh; Srivastava, Trisha; Benny, Altrin D. S.; Garg, Neeraj (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Nasopharyngeal tuberculosis is an uncommon presentation, often posing a diagnostic challenge due to its rarity and the non-specific nature of its symptoms, which can mimic other more common ENT conditions. Tuberculosis is a multi-systemic disease affecting almost any part of the body. Primary nasopharyngeal tuberculosis is described as an isolated infection of the nasopharynx in the absence of pulmonary or systemic disease. A 38-year-old female patient presented to ENT department with complaints of nasal obstruction, cough. On flexible fiberoptic nasal endoscopy, nasopharyngeal mass was seen occupying whole of the nasopharynx. The mass had irregular surface with few necrotic areas over the surface. Post op recovery was uneventful. Final histopathology report came out to be suggestive of granulomatous disease with caseous necrosis. Patient has been on regular follow for the same and she has been showing adequate recovery with the medications. Nasopharyngeal tuberculosis is an uncommon presentation, often posing a diagnostic challenge due to its rarity and the non-specific nature of its symptoms, which can mimic other more common ENT conditions. Given the complexity and rarity of this condition, a meticulous, multidisciplinary approach was essential for accurate diagnosis and effective management. The patient was promptly initiated on an Anti-Koch’s Therapy (AKT) regimen following confirmation of the diagnosis through advanced imaging and histopathological analysis. Her consistent and marked improvement on AKT underscores the importance and efficacy of a collaborative treatment strategy in managing such rare and complex ENT cases.